IMPACT OF THE AWARENESS SESSION AND WORKSHOP ON GOOD SAMARITAN LAW ON MEDICAL UNDERGRADUATES: A CROSS SECTIONAL STUDY (Journal of Forensic Medicine & Toxicology, 2023)
Introduction: Any person who comes forward to help in emergency with the only intent of saving a life is a Good Samaritan. India accounts for a large number of deaths occurring due to traffic accidents, the timely intervention by bystanders has suggested to reduce the number of deaths drastically. Medical professionals and students being challenged with responsibilities of saving lives, forms the basis of the study to explore and contribute to the knowledge on this law. Objective: To assess the awareness, willingness and the impact of the workshop on the Good Samaritan Law among the medical undergraduates. Methodology: A cross sectional, pre post interventional type of a study was carried out with a total of 306 medical college students in Maharashtra were assessed by collecting responses by a structured questionnaire. A workshop session was carried out and the responses were gathered post workshop. Observations 51.96% were aware of the law. Amongst students who chose to intervene, 76.40% had road and traffic related setting followed by railways. The major reason for hesitation amongst the people who decide not to intervene was that 31.69% lacked skill and 30.39% feared legal hassles. Post workshop 13% more (p value 0.0009) students said that they would intervene, 12.69% more felt confident (p value 0.0075), 69.7% (p value 0.0041) voted to include the law in the curriculum and 10-20% subjective increment was noted in knowledge, skills, behavioural change and other fields. Conclusion: With the workshop and the awareness session we found a significant increase in various aspects amongst the medical undergraduates. A regular curriculum-based teaching would help to reduce the number of mortalities in accidents and sudden deaths if one behaved as a Good Samaritan and didn’t fear the legal hassles.
Keywords: Samaritan; Law; Emergency; Accidental Deaths